COOPERATIVE VIRTUAL GENERAL ASSEMBLIES AND COOPERATIVE PRINCIPLES. A LEGAL AND EMPIRICAL ANALYSIS - Meira, Deolinda (International Journal of Cooperative Law, 2023)
Cooperatives must achieve the digital transition in its various dimensions. New technologies must be put at the service of promoting democratic participation, supporting democratic management, and bringing cooperators closer to the cooperative. Virtual general meetings can be a way of consolidating the cooperative principle of democratic member control. In turn, the principle of education, training, and information may enhance the digital transition in cooperatives and promote virtual general meetings. The pandemic caused by COVID-19 forced social distancing to deal with health restrictions, which boosted internal digital-based organisational processes, including general assemblies. The results of the COOPVID Project show that in some cooperatives the general assemblies that were held via videoconference had more participation than when they were held in person and some cooperatives are already thinking about changing the model of how meetings will be held during the post-pandemic period. The project also highlighted that in general the cooperatives do not use the reserve for education and training to combat digital illiteracy.